Decisions at the Brink: Locomotor Experience Affects Infants’ Use of Social Information on an Adjustable Drop-off - Karasik, Lana B.; Tamis-LeMonda, Catherine S.; Adolph, Karen E. (Frontiers in Psychology, 2016)
How do infants decide what to do at the brink of a precipice? Infants could use two sources of information to guide their actions: perceptual information generated by their own exploratory activity and social information offered by their caregivers. The current study investigated the role of locomotor experience in using social information—both encouragement and discouragement—for descending drop-offs. Mothers of 30 infants (experienced 12-month-old crawlers, novice 12-month-old walkers, and experienced 18-month-old walkers) encouraged and discouraged descent on a gradation of drop-offs (safe “steps” and risky “cliffs”). Novice walkers descended more frequently than experienced crawlers and walkers and fell while attempting to walk over impossibly high cliffs. All infants showed evidence of integrating perceptual and social information, but locomotor experience affected infants’ use of social messages, especially on risky drop-offs. Experienced crawlers and walkers selectively deferred to social information when perceptual information is ambiguous. In contrast, novice walkers took mothers’ advice inconsistently and only at extreme drop-offs.